2013
DOI: 10.3109/0142159x.2013.858111
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of a facilitated peer mentoring program

Abstract: Involvement in the facilitated peer mentoring program was associated with increased skills and academic activities for most participants. Future studies are needed to assess its applicability and success among various demographic groups in academic medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 47 publications
(61 reference statements)
1
66
0
Order By: Relevance
“…The results showed that teaching delivered by educated TAs rendered higher marks than teaching by self‐learned TAs. Similar results have been described by others (McKenna and French, ; Yu et al, ; Mayer et al, ). Importantly, the variability decreased and the lower marks became much rarer.…”
Section: Discussionsupporting
confidence: 92%
“…The results showed that teaching delivered by educated TAs rendered higher marks than teaching by self‐learned TAs. Similar results have been described by others (McKenna and French, ; Yu et al, ; Mayer et al, ). Importantly, the variability decreased and the lower marks became much rarer.…”
Section: Discussionsupporting
confidence: 92%
“…In single institution studies of junior faculty, mentored faculty (36%) were more likely to be men (odds ratio: 2.9) and clinician‐scientists (odds ratio: 10.3). In addition, mentored clinician‐educators reported spending significantly more time on scholarly activity (20.6% vs 11.5%, p < .01) and higher levels of self‐efficacy in career and skill development, academic success (awards, grants, teaching/mentoring, publications), career satisfaction, and scholarly productivity …”
Section: Introductionmentioning
confidence: 99%
“…In addition, mentored clinician-educators reported spending significantly more time on scholarly activity (20.6% vs 11.5%, p < .01) 8 and higher levels of self-efficacy in career and skill development, 9,10 academic success (awards, grants, teaching/mentoring, publications), 11 career satisfaction, 12 and scholarly productivity. 13,14 A series of studies has focused on mentoring of research careers in academic medicine. 4,[15][16][17][18][19] One national study conducted a decade ago reported that the 54% of junior faculty who were mentored perceived more institutional support for teaching, research, and administration; allocated more time to research each week; were more satisfied at work; and believed they had better research skills.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, women experience greater challenges in procuring effective mentorship and it does remain a key factor in career progression . Well‐organized programmes do appear to help, and the changes brought about by mentoring of women can be sustained . Clear boundaries need to be in place as sexual harassment has been reported …”
Section: Special Circumstances (Gender and Cross‐cultural)mentioning
confidence: 99%